How Does the Starting Order in the First and Second Run Affect the Final Rank in the FIS World Cup Giant Slalom? - Glenn Björklund; Mikael Swarén; Mikael Swarén (Frontiers Media S.A., 2022)
The aim of this study was to determine the impact of runs 1 and 2 on overall rank in Giant Slalom. Data from 15 seasons (2005/2006-2019/2020) including and unique starts for women (n = 2,294) and men (n = 2,328) were analyzed. Skiers were grouped based on final ranks 1-3 (G3), 4-10 (G10), and 11-20 (G20) and separately analyzed for women and men. A Wilcoxon-signed rank test was used for comparisons between runs 1 and 2, while a multi-nominal logistic regression was used to identify odds ratios (OR) associated with group rank. Women had similar run times for runs 1 and 2 (p = 0.734), while men had faster times on run 2 (p < 0.001). The strongest association to G3 was during run 1 for run time (men: OR 1.06-1.12; women: OR 1.06-1.11, all p < 0.01) and gate-to-gate times (men: OR 33-475; women: OR 81-2,301, all p < 0.001). Overall, this study demonstrates the importance of a fast first run for improving the final ranking group and the need to increase the tempo going from the first to the second run for men.